Yield and chemical components from the constitutive parts of olive (cv. Genovesa) fruits are barely affected by spring deficit irrigation - Pierantozzi, Pierluigi (2021)
An important concern for the expansion of olive production is related to the irrigation water availability. This study was driven on the hypothesis that regulated deficit irrigation (RDI) during spring - a period covering basically the fruit set, the seed development and the seed/pit hardening - does not affect significantly yield and chemical components from cv. Genovesa olive fruits. The objectives were twofold: a) to evaluate productive responses to RDI treatments, and b) to gain further information on the effect of irrigation on yield and chemical components from the constitutive parts of the olive fruit. To test the hypothesis, data of selected productive and quality parameters obtained from trees of three RDI treatments were tested and compared with those from full-irrigated trees. Results showed that over a 3-year period, water restriction had no effects on fruit pulp dry matter accumulation. Neither were significant effects on oil accumulation and fatty acid composition from both oil-bearing tissues (pulp and seed). Both tocopherols and total phenols (TP) from pulp were unchanged among RDI. Conversely, significant and opposite tendencies were noted for these parameters from the seeds: deficit irrigation caused lower amounts of α-tocopherol but higher TP than the full-irrigated treatment. Overall, results indicate that spring water restriction can save a significant amount of irrigation water with minor impact on important productive and quality parameters.